2018
DOI: 10.29173/jchla29366
|View full text |Cite
|
Sign up to set email alerts
|

Research Support in Health Sciences Libraries: A Scoping Review

Abstract: Background:As part of a health sciences library’s internal assessment of its research support services, an environmental scan and literature review were conducted to identify research services offered elsewhere in Canada. Through this process, it became clear that a more formal review of the academic literature would help libraries make informed decisions about their services. To address this gap, we conducted a scoping review of research services provided in health sciences libraries contexts.Methods:Searches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…Under this kind of budget constraint, we were surprised to find that 5 respondants reported that they had all the databases or resources they needed to support research. Similar to previous studies [7] our study found that the majority of projects supported were literature studies, followed by support for clinical studies. This is not surprising as evidence-based medicine is a priority in many healthcare organizations and both systematic reviews and clinical trials are cornerstones of scientific evidence.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Under this kind of budget constraint, we were surprised to find that 5 respondants reported that they had all the databases or resources they needed to support research. Similar to previous studies [7] our study found that the majority of projects supported were literature studies, followed by support for clinical studies. This is not surprising as evidence-based medicine is a priority in many healthcare organizations and both systematic reviews and clinical trials are cornerstones of scientific evidence.…”
Section: Discussionsupporting
confidence: 89%
“…Hospital librarians typically support the research process in traditional ways, doing literature searches, providing articles, resources and expertise as needed. A scoping review found that research support provided by health sciences librarians was predominantly for systematic review support, though there was an emerging role in data management support [7]. Another study described a team of clinicians and librarians who created an online workspace using web 2.0 tools for use by researchers within their hospital.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the historical overview of the use of bibliometrics in medicine might contribute to the knowledge, which a health librarian can use to improve his everyday work, following the Palmer and Colton (1978, p. 118) claim, that ‘mayor value of history, historians, and methods of historical thinking is not in their contribution of and to things past, but in the knowledge and involvement history establishes in everyday people in everyday world’. As recent studies show, the inclusion of new services like bibliometrics is essential in the state of the art health libraries (Åström & Hansson, 2013; Dexter et al, 2019; González‐Alcaide & Poveda‐Pastor, 2018; Visintini, Boutet, Manley, & Helwig, 2018; Xie & Zhang, 2018).…”
Section: Introductionmentioning
confidence: 99%